Versatility of Maxillary Antrum: Insights from Clinical Practice and Radiologial Evidence - SRIVASTAVA, MADHUMITA; KUMAR, ANAND; MARKANDEY, ADITYA SUNIL; VISHAL, GAURAV (Indian Journal of Case Reports, 2026)
Knowledge about neighbors is essential to have a peaceful existence, that’s about antrum pathology. The maxillary sinus impacts most on the work of maxillofacial surgeons, as it often requires making a diagnosis in relation to orofacial pain that may be sinogenic in origin. This case series aimed to analyze diverse maxillary sinus diseases, identify diagnostic challenges, and distinguish sinogenic conditions from dental and other pathologies through clinical and radiological assessment. Various cases of suspected maxillary sinus pathology presenting to the Oral and Maxillofacial Surgery Outpatient Department, Bokaro General Hospital, Jharkhand, were reviewed. Detailed history and clinical examination were supplemented with radiological investigations, including occipitomental radiographs and orthopantomograms. Computed tomography and magnetic resonance imaging were performed selectively to determine disease extent. Histopathological examination was undertaken when indicated. Cases comprised inflammatory, cystic, fungal, traumatic, fibro-osseous, and neoplastic lesions. The series underscores the importance of comprehensive evaluation and appropriate imaging for accurate diagnosis and effective treatment planning.